Bioecological Properties Of The Psylla Pyri L - Yuldasheva Shokhista Kobiljonovna; Teshaboyeva Maftuna Ikromjonovna (Zien Journals, 2025)
This article discusses the bioecological characteristics of the sucking insect pest Psylla pyri. The adult form and larvae of the insect cause damage by sucking the sap from the shoots, stems, leaves and fruits of the pear plant and secrete a sugary sticky liquid. As a result, vital processes in various organs of the plant are disrupted, the leaves darken and fall off, the fruits become hard and dehydrated, and the plant weakens, which leads to a significant decrease in the yield of the following year.
Keywords: pear psylla; pest; population density; yield